Chemical Synthesis of the Repeating Unit of Type Ia Group B Streptococcus Capsular Polysaccharide - Mondal, Prolay K. (Org Lett, 2015)
[Image: see text] The structure of the capsular polysaccharide (CPS) of serotype Ia group B Streptococcus (GBS) has been characterized for years, but its repeating unit, which is a challenging pentasaccharide with a branch and a difficult α-sialic acid linkage, has not been synthesized yet. In this report, an effective synthesis was developed for the serotype Ia GBS CPS repeating unit, which had a reactive functionality linked to its main chain reducing end to enable further elaboration, such as coupling with carrier proteins. The target molecule was accomplished by a convergent [2+3] glycosylation strategy employing a sialo-disaccharide as donor and a branched trisaccharide as acceptor. The strategy was designed to suit the synthesis of oligomers of the repeating unit.